2020
DOI: 10.3390/plants9020204
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Phytochemical Analysis Reveals the Alteration of Plant Hormones, Characteristic Metabolites, and Related Gene Expression in Tea (Camellia sinensis L.) Leaves During Withering

Abstract: Plant hormones play an important role in the chemical metabolism of postharvest plants. However, alterations in plant hormones of postharvest tea and their potential modulation of quality-related metabolites are unknown. In this study, the dynamic alterations of abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA), and critical metabolites, such as catechins, theanine, and caffeine, in tea leaves were analyzed during withering from 0 to 24 h. It was found that the ABA content increased from 0 to 9 h bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…Interestingly, compared with the water retention treatment, ABA content continued to increase and remained at a higher level under the dehydration treatment. This is consistent with the results in previous reports [ 20 , 42 ]. In the WGCNA analysis, CsPDX2.1 was found in the module with the highest positive correlation to ABA, indicating that the expression pattern of CsPDX2.1 during withering was significantly correlated with ABA content.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, compared with the water retention treatment, ABA content continued to increase and remained at a higher level under the dehydration treatment. This is consistent with the results in previous reports [ 20 , 42 ]. In the WGCNA analysis, CsPDX2.1 was found in the module with the highest positive correlation to ABA, indicating that the expression pattern of CsPDX2.1 during withering was significantly correlated with ABA content.…”
Section: Discussionsupporting
confidence: 94%
“…Previously, we found that L-theanine decreased gradually with the loss of water during withering, and transcriptome analysis showed that ABA might potentially regulate L-theanine metabolism [ 20 ]. Therefore, to further investigate whether moisture content was the key factor involved in L-theanine catabolism in tea leaves, we established three treatments, a withering treatment, a water retention treatment, and a water loss treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important roles of plant hormones in resistance to abiotic stresses have been emphasized [27][28][29], including mediation of salt stress to regulate plant adaptation [30]. Many studies have showed that the expression of genes related to phytohormones depends on the severity and/or duration of abiotic stresses [31,32], indicating that changes in the expression of phytohormone-related genes need to be characterized with respect to stress duration. Therefore, the aim of the present study was to use the transcriptome samples of tissues of Jerusalem artichoke exposed to salt stress for different durations to characterize the expression patterns of genes (especially those related to phytohormone signal transduction).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have showed that the expression of genes related to phytohormones depends on the severity and/or duration of abiotic stresses [25,26], indicating that changes in the expression of phytohormone-related genes needs to be characterized with respect to stress duration. Therefore, the aim of the present study was to use the transcriptome samples of tissues of Jerusalem artichoke exposed to salt stress for different durations to characterize the expression patterns of genes (especially those related to phytohormone signal transduction).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%